Trends and Determinants of Health Status of Chronically Ill Older Adults In China 2013–2020: A National Panel Data Analysis - Hongyan Wang; Cai Liu (Scientific Journal Of Humanities and Social Sciences, 2026)
Background: With the accelerating ageing of the population and changes in the disease spectrum, demand for elderly care and healthcare continues to rise, placing significant pressure on public finances. Exploring the factors influencing the health of older people and identifying emerging trends has therefore become essential for improving their health and reducing expenditure on healthcare.Objective: Drawing on the CHARLS database, this study analyses differences in the health status of middle-aged and older adults across age groups from temporal, spatial and health measurement perspectives, with a view to providing new insights for improving the health of older people.Methods: By constructing panel data and employing a fixed-effects model, with ADL, CESD and SP designated as the three explanatory variables, this study examined the factors influencing the physical and mental health as well as social participation of older adults.Results: Regarding trends in the physical health status of middle-aged and older adults between 2013 and 2020, ADL scores were inversely correlated with physical health status; higher scores indicated poorer health. Regarding the mental health status of middle-aged and young older adults from 2013 to 2020, CESD scores were inversely proportional to mental health status; the higher the CESD score, the poorer the mental health status. With regard to social participation among this group during the same period, social participation scores were directly proportional to health status; the higher the score, the greater the level of social participation.Conclusion: This study examines the factors influencing the health of older adults from three dimensions, whilst also conducting a comparative analysis of the health status of older adults across different age groups. To improve the physical and mental health and social participation of older adults, efforts should be made to develop education for older adults, prioritise emotional communication and social recognition among them, and alleviate the psychological stress associated with loneliness.